Analisis Faktor Faktor Produksi Usahatani Padi Sawah di Kota Padang - Dani Hardianti; Dian Hafizah; Hasnah Hasnah (Pusat riset dan Inovasi Nasional, 2026)
The factors influencing lowland rice production in Padang City are the focus of this study. The study was conducted through a field survey of lowland rice farmers to obtain primary data relevant to farming activities. The analysis method used was multiple linear regression with the dependent variable being lowland rice production (Y) and independent variables including land area (X₁), seeds (X₂), fertilizer (X₃), labor (X₄), and farming experience (X₅). The research findings show that simultaneously all production factors, including land area, seeds, fertilizer, labor, and farming experience, have a significant effect on lowland rice production in Padang City. Partially, the variables of fertilizer and labor have a significant effect on lowland rice production, while land area, seeds, and farming experience have no significant effect. These findings indicate that the increase in lowland rice production in Padang City is more determined by input intensification efforts, particularly through appropriate fertilization and labor availability, compared to land expansion. As a result, agricultural policies need to be directed at increasing input efficiency to support the productivity and sustainability of rice farming.